Flow diverters in the treatment of unruptured vertebral artery dissecting aneurysm: A single-center experience - Lu, Xiaoyang; Zhang, Yuansheng; Zhou, Hu; Jian, Lipeng; Yin, Shi; Li, Tao; Huang, Wei (Frontiers in Neurology, 2023)
Objective To evaluate the efficacy and safety of flow diverters (FD) in the treatment of vertebral artery dissecting aneurysm (VADA). Methods A total of 16 patients with 17 unruptured VADAs treated with FD from January 2017 to May 2021 were included. Data of clinical outcomes and radiographic examination were collected and assessed by the modified Rankin Scale (mRS) and O'Kelly-Marotta (OKM) grading scale. Results All patients were treated with a single FD. No perioperative complications occurred. The mean age was 55.1 years old. The mean size of the aneurysm was 10.4 mm. All patients had a favorable occlusion (OKM D + C3) result and the complete occlusion rate in the 6th month was 66.7% (OKM D). The mean clinical follow-up time was 7.8 months, and all patients had a good clinical outcome (mRS = 0). No procedure-related complication occurred at the last follow-up time. Conclusion FD is an effective and safe tool for treating unruptured VADA. Long-term prospective studies with a large sample are still needed to confirm these findings in the future.